Extensive responses of lake dynamics to climate change on northeastern Tibetan Plateau - Liu, Wenhui; Liu, Hairui; Li, Qingpeng; Xie, Changwei; Zhang, Zhijun; Zhou, Guanghao; Zhang, Qi; Zhao, Qinhao (Frontiers in Earth Science, 2023)
The lakes on the Qinghai–Tibetan Plateau (QTP) have undergone substantial changes. As intensive cryospheric components change, the response of the lake dynamics to climatic factors, glacier-snow melting, and permafrost thawing has been complex. Based on Landsat images, meteorological data, and glacier and permafrost data, the spatial-temporal changes in the lake area on the northeastern Tibetan Plateau between 1988 and 2019 were analyzed and the driving factors behind the lake changes were further explored. The results suggest that the regional lake area increased from 1988 to 2019 at rates of 0.01–16.03 km2/yr. It decreased during 1988–2000, quickly increased during 2000–2012, and rapidly increased during 2012–2019. The most significant lake expansion occurred in sub-region I, which is the source region of the Yangtze River Basin. There was a sharper increase during 2012–2019 than during 2000–2012 in sub-region II (the source region of the Yellow River Basin and the Qinghai Lake Basin) and sub-region III (the Qaidam Basin). The significant lake expansion occurred about 12 years earlier in sub-region I than in sub-regions II and III. This dramatic change in the lake area was closely associated with the annual precipitation, and precipitation was the primary driving factor. Although serious glacier retreat occurred, most of the lakes in the sub-regions were non-glacier-fed lakes. The correlation between glacier ablation and the change in the lake area was poor, which suggests that glacial meltwater was not the replenishment source of most of the lakes in this region. A more accelerated increase in the active layer thickness occurred (1.90 cm/yr), which was consistent with the more rapid lake expansion, and the permafrost degradation further intensified the lake expansion.